THE USE OF PLAYDOUGH, UNO STACKO, KINETIC SAND, AND FLASHCARDS IN IMPROVING THE AL QUR’AN READING SKILL FOR STUDENTS WITH DYSLEXIA DURING PANDEMIC OF COVID-19 - Laily Nur Arifa (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Covid-19 pandemic requires students to study at home without interacting in class for a while. Learning from home is undoubtedly difficult for early childhood and elementary school students, especially students with special needs, including dyslexia. Many studies aiming to improve the alphabet based-reading skill for children with dyslexia have been conducted; nevertheless, further study on Al-Qur’an reading skill for these children in Indonesia as a country with the majority of Muslim inhabitants is considered essential. The different characteristics between Latin and Arabic alphabets create a complex challenge for dyslexic students. Arabic as a foreign language whose written form is rarely found publicly has made dyslexic children less exposed to Arabic alphabetical forms. This study is of single-subject experiment type and uses the A-B-A design. The intervention stage comprises four media, namely Uno stacko, flashcard, kinetic sand, and playdough. The study results prove 0% overlap, and the intervention is proven to be successful in improving the Al-Qur’an reading skill of students with dyslexia significantly.